Reflexiones interculturales en la obra de Bernat Metge: una revisión sociocultural de un autor «al margen de la ley». - SANTOS-SOPENA, ÒSCAR O. (Scripta, 2020)
As evidenced by the numerous researches carried out since the 19th Century the Catalan writer Bernat Metge (1340 / 46-1413) is one of the key authors of Catalan literature. In this research, we understand Metge as controversial writer, an «outside the law» author who writes works such as Llibre de Fortuna e Prudència (1381) and Lo somni (1399) that through words, irony, and humor narratively develops their political issues and it helps to prove his innocence in some of the open penal processes against him, while at the same time raising some of the philosophical problems of European Humanism (Batllori 1995; Butiná 2007; Gómez Moreno 2011). This study highlights the use of satirical humanist dialogue that helps to understand and promote the origin of modernity and the existence of humanistic thought in Catalan literature.